(3ebGdI aj efGaY Gddjehfs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3bGd PcQJ CjgG GdCN GdcQje ai cKjQ ef CZQGVge eY XghQ Ldjd efGaYI EPG hVY ai ehGVYg s
(3BNQgG (B:s
(3UaI Yed Nd Gddjehf jYSQ Gddjehf Ydi TF jSjQ ef GdedM HbOQ eG jMaXI ef GdJeQQ hJQaY Ydi GdfGQ ai bOQ HQGe hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs